PERBEDAAN KARAKTERISTIK LINGKUNGAN BERDASARKAN TINGKAT ENDEMISITAS DBD DI KELURAHAN GELANGAN - Annisa Bekti Rohmatus; Henry Setyawan Susanto; Mateus Sakundarno Adi; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Dengue Hemorrhagic Fever (DHF) is classified as an infectious disease transmitted by Aedes sp. Mosquitoes. Gelangan is a DHF endemic village with an increase in Incidence Rate (IR) values for 2017-2019, based on IR RW there are high and low endemic RWs, there are no studies on environmental characteristics that distinguish between high and low endemic areas so research is conducted to see differences in characteristics environment based on the level of DHF endemicity in the Gelangan village. The design of this research is comparative descriptive type. The research subjects were in the form of Gelangan sub-district with 5 RW for high endemic DHF category and 5 RW for low endemic DHF category. The results of the study are that the RW category with high endemic population has a majority population occurring in the category of sparse population density, wider RW land area, land use that appears to be in vegetation near housing, rice fields and gardens that can search for vector nests, air temperatures higher than low endemic RW. The RW category with low endemic areas is in a moderate population density, with RW land not too large, the land use is less vegetation, rice fields or gardens than RW with endemic areas. The conclusion obtained from this study is the environmental characteristics have differences at each level of DHF endemicity of each RW based on the mapping that has been done is population density, land use, and air temperature while there is no difference in each region is air humidity